Homes - Hall, Margaret (Oxford Heinemann Library, 2002)
Looks at the different types of homes people live in around the world. Suggested level: junior, primary.
Include Color Illustration, Index and Glossary
Keywords: Dwellings -- Architecture, Domestic -- Big books